Stagnation point flow over a stretching permeable sheet in a micropolar fluid - Anuar Ishak,; Roslinda Nazar, (Penerbit ukm, 2009)

(untitled)
The steady two-dimensional stagnation point flow of an incompressible micropolar fluid over a stretching permeable sheet is considered. The stretching velocity and the ambient fluid velocity are assumed to vary linearly with the distance from the stagnation point. The governing partial differential equations are transformed into ordinary differential equations using similarity transformation, before being solved numerically by the Keller-box method. The features of the flow characteristics are analysed and discussed. Comparison of the results of this study with the existing results for some particular cases has been done and found to be in excellent agreement. It is also observed that suction increases the skin friction coefficient whereas injection decreases it